Low dose of caffeine enhances the efficacy of antidepressants in major depressive disorder and the underlying neural substrates. Issue 8 (8th May 2017) - Liu, Qing‐Shan; Deng, Ran; Fan, Yuyan; Li, Keqin; Meng, Fangang; Li, Xueli; Liu, Rui
Abstract : Low dose of caffeine (60 mg, oral, 4 wk) produced rapid antidepressant effects in depressed patients. However, caffeine did not affect sleep as measured by overnight polysomnography. Moreover, chronic caffeine consumption elicited inhibition of hypothalamic–pituitary–adrenal axis. These findings indicated the potential benefits of caffeine to enhance the outcome of antidepressants treatment in major depressive disorder. Abstract : Scope: Caffeine is one of the most frequently used psychoactive substances ingested mainly via beverage or food products. Major depressive disorder is a serious and devastating psychiatric disorder. Emerging evidence indicates that caffeine enhances the antidepressant‐like activity of common antidepressant drugs in rodents. However, whether joint administration of low dose of caffeine enhances the antidepressant actions in depressed patients remains unclear. Methods and results: A total of 95 male inpatients were assigned to three groups and were asked to take either caffeine (60, 120 mg) or placebo (soymilk powder) daily for 4 wk on the basis of their current antidepressant medications. Results showed that chronic supplementation with low dose of caffeine (60 mg) produced rapid antidepressant action by reduction of depressive scores. Furthermore, low dose of caffeine improved cognitive performance in depressed patients. However, caffeine did not affect sleep as measured by overnight polysomnography. Moreover, chronic caffeine consumption elicited inhibition of hypothalamic–pituitary–adrenal axis activation by normalization of salivary cortisol induced by Trier social stress test. Conclusions: These findings indicated the potential benefits of further implications of supplementary administration of caffeine to reverse the development of depression and enhance the outcome of antidepressants treatment in major depressive disorder.